Pulmonary artery stiffness in chronic obstructive pulmonary disease (COPD) and emphysema: The Multi‐Ethnic Study of Atherosclerosis (MESA) COPD Study. Issue 1 (10th May 2017) - Liu, Chia‐Ying; Parikh, Megha; Bluemke, David A; Balte, Pallavi; Carr, James; Dashnaw, Stephen; Poor, Hooman D.; Gomes, Antoinette S; Hoffman, Eric A; Kawut, Steven M.; Lima, Joao A.C.; McAllister, David A.; et al.
Abstract : Purpose: Chronic obstructive pulmonary disease (COPD) and particularly emphysema are characterized by stiffness of the aorta, due in part to accelerated elastin degradation in the lungs and aorta. Stiffness of the pulmonary arteries (PAs) may also be increased in COPD and emphysema, but data are lacking. We assessed PA stiffness using MRI in patients with COPD and related these measurements to COPD severity and percent emphysema. Materials and Methods: The Multi‐Ethnic Study of Atherosclerosis (MESA) COPD Study recruited 290 participants, age 50–79 years with 10 or more packyears and free of clinical cardiovascular disease. COPD severity were defined on postbronchodilator spirometry by ATS/ERS criteria. Percent emphysema was defined as the percentage of regions of the lung < ‐950 Hounsfield units on full‐lung computed tomography (CT). PA stain was defined by the percent change in cross‐sectional PA area between systole and diastole on MRI. Blood flow across the tricuspid and mitral valves was assessed by phase‐contrast MRI for determination of the ventricular diastolic dysfunction (E/A ratio). Results: PA strain was reduced in COPD compared with controls ( P = 0.002) and was inversely correlated with COPD severity ( P = 0.004). PA strain was inversely associated to percent emphysema ( P = 0.01). PA strain was also markedly correlated with right ventricular diastolic dysfunction measured by E/A ratios in the fully adjusted mix models ( P = 0.02). Conclusion: PA strain is reduced in COPD, related in part to percent emphysema on CT scan, which may have implications for pulmonary small vessel flow and right ventricular function. Level of Evidence : 2 Technical Efficacy : Stage 1 J. Magn. Reson. Imaging 2018;47:262–271.